Development of PAN (personal area network) for Mobile Robot Using Bluetooth Transceiver - Choo, S. H; H. M. Amin, Shamsudin; Fisal, Norsheila; Yeong, C. F.; Abu Bakar, J. (2003)

(untitled)
In recent years, wireless applications using radio frequency (RF) have been rapidly evolving in personal computing and communications devices. Bluetooth technology was created to replace the cables used on mobile devices. Bluetooth is an open specification and encompasses a simple low-cost, low power solution for integration into devices. This research work aim was to provide a PAN (personal area network) for computer based mobile robot that supports real-time control of four mobile robots from a host mobile robot. With ad hoc topology, mobile robots may request and establish a connection when it is within the range or terminated the connection when it leaves the area. A system that contains both hardware and software is designed to enable the robots to participate in multi-agent robotics system (MARS). Computer based mobile robot provide operating system that enabled development of wireless connection via IP address.